(untitled) (Journal Of Educational and Psychological Researches, 2025)
The research aims to identify the affiliation motivation of university teachers in terms of gender, academic specialization, university sector (public, private), and the scientific rank of university teachers (professor, assistant professor, lecturer, assistant lecturer). To achieve this, a sample of 500 male and female teachers from the University of Baghdad, Al-Farahidi University College, and Sadr Al-Iraq University College were chosen for the academic year (2023-2024). To collect the needed data, a scale of 20 items designed by (Hill, 1987) to measure affiliation motivation was adopted. The results showed that university teachers have affiliation motivation. There are no statistically significant differences in the affiliation motivation among university teachers in terms of gender and specialization (scientific, humanities). There are statistically significant differences in affiliation motivation among university teachers according to the sector of university (private and public), in favor of public universities. Finally, there are statistically significant differences in affiliation motivation among university teachers according to the scientific rank, in favor of the assistant lecturer and lecturer. In light of the results, the researchers developed a set of conclusions, recommendations, and suggestions.